Development and Functional Evaluation of a Smart Mom–Integrated Prototype for Real-Time Fetal Stress Monitoring - Deswani Deswani; Andi Sari Bunga Untung; Indra Gunawan; Nina Primasari (Poltekkes Kemenkes Jakarta III, 2026)
Fetal movement is a critical indicator of fetal well-being, yet practical devices integrated with digital interventions for direct, objective monitoring remain limited. This study aimed to develop and evaluate the functionality and safety compliance of the Smart Mom–Integrated Prototype for real-time fetal movement monitoring. Employing a Research and Development (R&D) approach, the prototype was developed using an accelerometer sensor, an ATmega328P microcontroller, an OLED display, and Bluetooth connectivity integrated with an Android application. The device underwent a rigorous four-stage evaluation: (1) simulated testing for initial movement detection accuracy; (2) laboratory functional testing for overall system performance; (3) safety testing based on the SNI IEC 60601-1 standard; and (4) limited clinical/user testing involving five third-trimester pregnant women (32–38 weeks gestation) monitored for 15–30 minutes.In simulated testing, the device achieved an initial fetal movement detection accuracy rate of 85%. Laboratory functional testing demonstrated a 93% system operation success rate with clear data visualization and stable Bluetooth transmission. Safety testing indicated that the device's surface temperature reached 35.2°C after eight hours of continuous use, with 0.0 mA leakage current and no reported skin irritation. In limited clinical testing, the device successfully recorded a mean of 20.6 movements per 30 minutes. Concurrently, maternal stress scores (PSS-10) decreased significantly post-intervention (22.40 ± 3.13 to 15.80 ± 2.28; p = 0.005). Data sensitivity in the field was moderately influenced by maternal Body Mass Index (BMI) and biological motion artifacts. The Smart Mom–Integrated Prototype demonstrates functional feasibility and safety compliance for home-based screening. Future development should focus on refining signal processing algorithms to mitigate maternal biological artifacts alongside validation trials against clinical gold standards.